Microguided endodontics: A case report of conservative approach for the management of calcified maxillary lateral incisors - Gurveen Kaur; Kondas Vijay Venkatesh; Dhanasekaran Sihivahanan (Wolters Kluwer Medknow Publications, 2021)
Pulp canal calcification due to dental trauma is described by hard-tissue deposition within the root canal space causing partial or complete obliteration and difficulty in locating canals. Endodontic treatment becomes difficult with increased risk for iatrogenic damage. Guided endodontics is a recent and an alternative solution in such cases. In this case report, a 28-year-old male patient reported with a chief complaint of pain in maxillary lateral incisors and a history of dental trauma that was diagnosed as pulpal necrosis with symptomatic apical periodontitis. The intraoral radiograph was taken, and apical radiolucency was confirmed with cone-beam computed tomography (CBCT) scan. A guided approach was decided for the location of the pulp canal with the use of microendodontic burs. A CBCT scan and an optical surface scan were performed and aligned using software for virtual template designing. The three-dimensional-printed template was positioned on to the tooth and with the help of microendodontic burs; the canal was located and biomechanically prepared using hand instruments. The root canal was obturated, and the cavity was sealed with a composite resin. This method demonstrated an ultraconservative, highly reliable, and successful treatment without the excessive removal of enamel and dentin.